2017
DOI: 10.1177/1934578x1701200602
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Cytotoxic Activities of Polysaccharides Extracted from Four Tropical Seaweed Species

Abstract: Polysaccharides extracted from Rhodymenia pseudopalmata, Solieria filiformis, Hydropuntia cornea (Rhodophyta) and Sargassum fluitans (Phaeophyceae) were evaluated for its cytotoxic and antiviral activities against Herpes simplex virus (HSV-Type 1). Chemical structures were characterized by FT-IR spectroscopy and 13 C-NMR analyses. Polysaccharides from Sargassum fluitans (EC 50 = 42.8 μg/ml) and Solieria filiformis (EC 50 = 136.0 μg/ml) showed antiviral activity against herpes simplex virus type-I in vitro at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…In general, dry weight and carbohydrate content were similar to those reported for other Solieria species [7,21]. S. filiformis from IMTA showed higher dry weight values than biomass from the control, corroborating the higher growth rate found in the IMTA system.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…In general, dry weight and carbohydrate content were similar to those reported for other Solieria species [7,21]. S. filiformis from IMTA showed higher dry weight values than biomass from the control, corroborating the higher growth rate found in the IMTA system.…”
Section: Resultssupporting
confidence: 84%
“…S. filiformis from IMTA showed higher dry weight values than biomass from the control, corroborating the higher growth rate found in the IMTA system. Total protein content was lower than previously reported for this species (15–20%) [21,30,31], while the lipid content was higher to other reports [31], and slightly higher from the IMTA biomass when compared to the control unit. In relation to the sulfate content, Morán-Santibañez et al [20] found significant lower sulfate content (7.5 ± 0.5%) than those reported in the present study.…”
Section: Resultscontrasting
confidence: 82%
See 3 more Smart Citations